Respuesta :

If [tex]p(x)[/tex] is a polynomial, then the zeros of [tex]p(x)[/tex] are the values of [tex]x[/tex] that satisfy [tex]p(x)=0[/tex].

So for (1), the zeros of [tex]f(x)=(x-4)(x-1)(x+3)[/tex] are the solutions to

[tex](x-4)(x-1)(x+3)=0\implies x=4,x=1,x=-3[/tex]

You can think of the multiplicity of each root as the number of times a root satisfies this equation. In this case, the multiplicity of each root is 1, because there is only one factor of [tex]x-4[/tex] or [tex]x-1[/tex] or [tex]x+3[/tex].

For (2), the zeros of [tex]g(x)[/tex] are the solutions to

[tex](x+1)(x-2)^2(x-4)=0\implies x=-1,x=2,x=4[/tex]

and the multiplicity of the zero [tex]x=2[/tex] is 2 because there are two factors of [tex]x-2[/tex] in [tex]g(x)[/tex]. The multiplicity of the other roots would be 1.

ACCESS MORE